Indigenous ectosymbiotic bacteria associated with diverse hydrothermal vent invertebrates - Goffredi, Shana K (ENVIRONMENTAL MICROBIOLOGY REPORTS, 2010)
P{>}Symbioses involving bacteria and invertebrates contribute to the biological diversity and high productivity of both aquatic and terrestrial environments. Well-known examples from chemosynthetic deep-sea hydrothermal vent environments involve ectosymbiotic microbes associated with the external surfaces of marine invertebrates. Some of these ectosymbioses confer protection or defence from predators or the environment itself, some are nutritional in nature, and many still are of unknown function. Several recently discovered hydrothermal vent invertebrates, including two populations of yeti crab (Kiwa spp.), a limpet (Symmetromphalus aff. hageni), and the scaly-foot snail (as yet undescribed), support a consortium of diverse bacteria. Comparisons of these ectosymbioses to those previously described revealed similarities among the associated microorganisms, suggesting that certain microbes are indigenous to the surfaces of marine invertebrates. In particular, members of the Thiovulgaceae (epsilonproteobacteria) and Thiotrichaceae (gammaproteobacteria) appear to preferentially form ectosymbioses with vent crustaceans and gastropods. Interactions between specific Proteobacteria and the surfaces of many marine invertebrates likely have ecological and evolutionary significance at these chemically challenging habitats.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)